The State-Religion Relationship from the Perspective of Islamic-Based State Policy - Effendi, Orien (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2022)
This article examines the relationship between state and religion from the perspective of Islamic-based state policy in Indonesia by focusing on how the state can manage the relationship with religion, as well as its impact on political, legal, and social structures. The data in this research is collected from primary and secondary legal materials. Using a juridical-normative approach and content analysis of various policies as well as conducting a literature review, this article concludes that in the context of state and religion relations, the state is not only considered as a political entity but also as a forum for implementing various Islamic-based values and principles in public policy. This article also sees that the state continues to make a positive legal system that is enforced nationally, in addition to efforts to introduce and apply moral and ethical values in the social and political structure of the state. In addition, this article also finds the fact that the relationship between the state and religion is still harmonious by providing legality to various Islamic-based legal products, one of which can be seen in sharia-based economic arrangements, especially Islamic banking. The relationship between state and religion in the Indonesian context shows that both have a reciprocal relationship that needs each other, state policies in ensuring religious life are very important to foster faith. Conversely, religion is very important for the state to get guidance in terms of morality. Keywords: State, Religion, Sharia Economics, Islamic Law.